Adsorption of basic dye on high-surface-area activated carbon prepared from coconut husk: Equilibrium, kinetic and thermodynamic studies - Tan, Ivy A. W.; Abdul Latif, Ahmad; Hameed, Bassim Hamid (Elsevier Ltd., 2008)
Adsorption isotherm and kinetics of methylene blue on activated carbon prepared from coconut husk were determined from batch tests. The effects of contact time (1–30 h), initial dye concentration (50–500 mg/l) and solution temperature (30–50 °C) were investigated. Equilibrium data were fitted to Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherm models. The equilibrium data were best represented by Langmuir isotherm model, showing maximum monolayer adsorption capacity of 434.78 mg/g. The kinetic data were fitted to pseudo-first-order, pseudo-second-order and intraparticle diffusion models, and was found to follow closely the pseudo-second-order kinetic model. Thermodynamic parameters such as standard enthalpy (ΔH°), standard entropy (ΔS°) and standard free energy (ΔG°) were evaluated. The adsorption interaction was found to be exothermic in nature. Coconut husk-based activated carbon was shown to be a promising adsorbent for removal of methylene blue from aqueous solutions.